An interesting case of pyrexia of unknown origin - Chinnasamy, Vignesh; Kumar, Mahendra (International Journal of Advances in Medicine, 2023)
Pyrexia of unknown origin (PUO) is defined as fever≥101°F on at least two occasions, illness duration of ≥3 weeks. Brucellosis is a bacterial infection caused by brucella species that includes Brucella canis, Brucella abortus, Brucella melitensis, and Brucella suis. They are gram-negative coccobacilli. They are non-motile, non-spore-forming, and facultative intracellular organisms. Kikuchi disease is a benign self-limiting disease, also referred to as histiocytic necrotizing lymphadenitis. Kikuchi disease mainly affects young women and usually presents as fever, lymphadenopathy and leucopenia. The manifestations are similar to brucellosis. Both coexist in a patient, which can be challenging for the treating physician. Here, we presented a case of brucellosis with coexisting Kikuchi disease.